ARSITEKTUR BALI BERKONSEPKAN ASTA KOSALA KOSALI DAN ASTA BUMI SEBAGAI DAYA TARIK WISATA - Suryawan IG. Agung Jaya (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2019)
Housing Traditional Balinese Settlements is a whole and round place with traditional patterns consisting of 3 elements, namely: elements of kahyangan tiga (village temple), elements of krama desa (residents), and Karang desa (region) against the background of norms and the traditional values that underlie it. The Housing of Traditional Balinese Settlements is based on concepts such as: a harmonious relationship between Bhuana Agung and Bhuana Alit, Ring Bead Cucupu, Tri Hita Karana, Tri Angga, Hulu-Teben to the birth of the Sanga Mandala value system that gives spatial directions , both in the scale of the house (home) and housing (village) based on the concept of the asta kosala kosali and asta bumi. Based on this concept by maintaining a noble culture based on literature inherited by the Balinese people, it is expected to be a humanist residence and bring good fibration to the people who died and become a tourist attraction. Keywords: Bali Architecture, Tourist Attraction